STUDY CARDIOTOXIC PROPERTIES OF NATIVE PEAT HUMIC ACIDS - M. V. Belousov; R. R. Akhmedzhanov; M. V. Zykova; L. N. Maslov; A. M. Guriyev; M. S. Yusubov (Бюллетень сибирской медицины, 2014)
The earlier pathomorphological  studies of toxic properties of peat humic acids (PHAs) at intraperitoneal injection revealed that one of the causes of lethality is the direct cardiotoxic action of PHAs. For the further study of the mechanism of cardiotoxic action, electrocardiogram was recorded and ventricular fibrillation threshold was determined in male rats after intraperitoneal injection of humic acids in knowingly lethal dose – 480 mg/kg bwt. A single  intraperitoneal injection  of PHA to rats in knowingly lethal dose caused a significant decrease of the ventricular fibrillation threshold in comparison with intact animals. It was found that the PHA injection exerted no significant effect on the heart rate in rats and change of the PQ, QT, and QTc intervals.  At the same time, the significant shortening of the QRS complex in comparison with intact animals was observed. Judging from the results obtained, the single injection of humic acids in the lethal dose induced a decrease in the electrical stability of heart, as evidenced by the drop of the ventricular fibrillation threshold. This decrease of the electrical stability of heart can be a cause of sudden cardiac death of trial rats. Disorder of the heart electrical stability is likely connected with the ionophoric action of humic acids and change of electrophysiological properties of cell membranes.